1986
DOI: 10.3354/meps033007
|View full text |Cite
|
Sign up to set email alerts
|

Implications of population dynamics and interspecific competition for harvest management of the seaweed Laminaria

Abstract: Growth rates and population variables of the seaweeds Laminaria longicruris De la Pylaie and L. digitata (Hudson) Lamouroux were monitored from July 1980 until April 1983 within adjacent harvested and control plots in southwestern Nova Scotia, Canada. Faster growth rates within the harvested plot, relative to the control plot, for new recruits of both species were detected only during the first year following a September 1980 total harvest of both species. Since standing crop had nearly recovered to pre-harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…After removal of the algal canopy, growth rates of the young sporophytes (stipe length between 25 and 50 cm in length) was twice as fast as that measured in the presence of the algal canopy. This is in agreement with what has been obtained from predicted growth rates of L. longicruris within a post-harvest population (Smith 1986), where growth of L. longicruris following harvesting was estimated to be 1.9 times faster relative to plants growing in an unperturbated mature kelp community.…”
Section: Discussionsupporting
confidence: 87%
“…After removal of the algal canopy, growth rates of the young sporophytes (stipe length between 25 and 50 cm in length) was twice as fast as that measured in the presence of the algal canopy. This is in agreement with what has been obtained from predicted growth rates of L. longicruris within a post-harvest population (Smith 1986), where growth of L. longicruris following harvesting was estimated to be 1.9 times faster relative to plants growing in an unperturbated mature kelp community.…”
Section: Discussionsupporting
confidence: 87%
“…15-20 m, growing in a more or less continuous band where there is suitable substratum (MacFarlane, 1952;Edelstein et al, 1969;Mann, 1972a;Tremblay & Chapman, 1980;Moore & Miller, 1983;Miller, 1985a;Novaczek & McLachlan, 1986;Scheibling, 1986;. However, with increasing exposure L. longicruris may co-exist with L. digitata in shallow water, and in shallow areas of extreme exposure L. digitata may replace its congener entirely (MacFarlane, 1952;Edelstein et al, 1969;Mann, 1972a;Smith, 1986). A similar pattern occurs in New England (Witman, 1987).…”
Section: Disturbance and Plant-plant Interactionsmentioning
confidence: 94%
“…The expected outcome of the recolonization following these disturbances should be the settlement of juveniles of Lessonia nigrescens within these openings, maintaining the belt in space and time. It is as yet unknown if a similar phenomenon occurs in populations of other kelp species, but Markham (1973), Dayton (1975a) and Smith (1986) have suggested that the seasonal reproductive pattern of species of Laminaria and Hedophyllum represent adaptive responses to seasonally predictable patches of substratum produced by storms. Thus, the phenomenon seems to be common among kelps.…”
mentioning
confidence: 99%